KESATUAN DALAM KEBERAGAMAN: PASANG SURUT PEMBAURAN ORANG-ORANG TIONGHOA DI SURABAYA - Sarkawi B. Husain (Faculty of Humanities, Jember University, 2013)
The Chinese migration to Surabaya can be traced back to the 14th Century. Among the push factors that forced the Chinese to migrate to Surabaya, poor conditions of living in their home country caused by natural disasters, warfares, and inhospitable environment were notable. In addition, the Chinese migrants in the 19th century were attracted by employment opportunities in colonial mines and plantations. Initially, there were no problems occuring between the Chinese and the indigenous peoples in Surabaya. The Chinese interacted with the indigenous people through marriage, religion, cultural performances, language, and food. However, their relations began to break down with the strengthening of the Dutch colonial rule in Indonesia. In the 19th Century, the colonial government began to introduce a number of regulations that effectively segregated the Chinese from the rest of population, namely the “wijkenstelsel”, an ethnic-based identification system (passenstelsel) and the establishment of Chinese schools. The postcolonial policies further disrupted the relations between the Chinese and the indigenous people. The policies included the Ekonomi Benteng, PP 10/59 which prohibited the Chinese and others identified as foreigners from engaging in village retail trade. Several additional policies established by the East Java Pepelrada (Regional Military Authority to Implement Dwikora) also discriminated against the Chinese in Surabaya.Keywords: assimilation, the Chinese, the indigenous people, Surabaya